KOOS and IKDC scales may be inadequate in evaluating patients with multiple ligament knee injuries: a systematic review. Issue 2 (23rd February 2016) - Wang, Dean; Yamaguchi, Kent T; Jones, Morgan H; Miniaci, Anthony
Abstract : Importance: Standardised, validated patient-reported outcome measures are crucial in understanding the impact of multiple ligament knee injury and surgery. Aim: Evaluate the validity and responsiveness of the Knee Injury and Osteoarthritis Outcome Score (KOOS) and International Knee Documentation Committee (IKDC) score in patients with multiple ligament knee injuries through existing studies in the literature. Evidence Review: A systematic review of the literature was performed using MEDLINE and Cochrane databases. The search terms 'multiple ligament, ' 'multiligament, ' 'knee dislocation, ' and 'combined ligament' were used in conjunction with 'KOOS' or 'IKDC'. Multiple ligament injury was defined as the disruption of ≥2 major knee ligaments. Validity was assessed through floor/ceiling effects, comparing scores between single and multiple ligament injuries, and correlation with Lysholm scores. Responsiveness was assessed by calculating effect sizes (ES) and standardised response means (SRM). Findings: 8 studies reported KOOS scores, and 45 studies reported IKDC scores. No studies specifically evaluated the validity or responsiveness of either measure in patients with multiligament knee injuries. Owing to a lack of available data, the validity and responsiveness of the KOOS could not be thoroughly evaluated. The IKDC may have a ceiling effect and indifference to the disparity between single and multiple ligament injuries, indicating poor content and construct validity. Correlations between IKDC and Lysholm scores ranged from 0.65 to 0.93. The IKDC demonstrated good responsiveness in this population, with ES and SRM ranging from 1.9 to 8.0 and 0.9 to 5.1, respectively. Conclusions and Relevance: The KOOS and IKDC may be inadequate in evaluating patients with multiple ligament knee injuries. Future studies should consider using the Multiligament Quality of Life (MLQOL) questionnaire, a recently developed multiligament knee injury-specific instrument, when evaluating patients with multiple ligament knee injuries.